2014
DOI: 10.1016/j.jacc.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Use and Outcomes of Ventricular Assist Devices Among Medicare Beneficiaries, 2006 Through 2011

Abstract: Objectives This study sought to examine trends in mortality, readmission, and costs among Medicare beneficiaries receiving ventricular assist devices (VADs) and associations between hospital-level procedure volume and outcomes. Background VADs are an option for patients with advanced heart failure, but temporal changes in outcomes and associations between facility-level volume and outcomes are poorly understood. Methods This is a population-based, retrospective cohort study of all fee-for-service Medicare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 36 publications
5
36
0
Order By: Relevance
“…[25][26][27] The centers vary in regard to the time frames studied and the proportion of BTT patients in the study populations, but the relatively high rates of hospitalization after LVAD implantation and the primary causes for readmission are remarkably homogeneous. In providing details on readmission trends that involved 2,507 LVAD implantations from 2006 through 2011, a Medicare database report 37 showed that the mean number of hospitalizations after LVAD implantation was stable at 1.8 ± 2.1 and that readmission rates were not affected by center volume.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] The centers vary in regard to the time frames studied and the proportion of BTT patients in the study populations, but the relatively high rates of hospitalization after LVAD implantation and the primary causes for readmission are remarkably homogeneous. In providing details on readmission trends that involved 2,507 LVAD implantations from 2006 through 2011, a Medicare database report 37 showed that the mean number of hospitalizations after LVAD implantation was stable at 1.8 ± 2.1 and that readmission rates were not affected by center volume.…”
Section: Discussionmentioning
confidence: 99%
“…For example, advanced heart failure patients are now commonplace in the CICU, as are temporary13 and permanent14 mechanical ventricular support devices. These devices may contribute to delirium given prolonged immobility and increased need for sedative medications.…”
Section: Etiology Of Icu Delirium: General and Cicu Specificmentioning
confidence: 99%
“…Diabetes mellitus is the most common cause of ESRD, and was the most common cause of ESRD among our cohort. Diabetes mellitus itself is associated with higher mortality and other adverse outcomes with VADs (including stroke, pump thrombosis, and device infection) 21, 40. As VADs are more commonly used, they are being implanted in people with higher comorbidity burden.…”
Section: Discussionmentioning
confidence: 99%
“…The claims also had to include diagnoses for HF or cardiogenic shock, in which case it was classified as primary therapy, or there had to be a claim within 30 days prior for a separate major cardiac surgery, in which case it was classified as post‐cardiotomy (Table S1). 20, 21 In 2005, before our study period, ICD‐9‐CM procedure codes were refined to distinguish implantable (37.66) and non‐implantable (37.62 and 37.65) ventricular assist devices 20. We required the VAD index date to be >30 days after the ESRD index date, which was obtained from the ESRD Medicare Evidence Report (Centers for Medicare & Medicaid Services Form 2728).…”
Section: Methodsmentioning
confidence: 99%